Analisys of flora of the Crimean Prisyvashya (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The results of analysis of systematic, arealogical, biomorphological and ecological structures of flora of Crimean Prisivashya is given. The flora includes 748 species of vascular plants from 344 genera, 80 families, 4 classes and 3 divisions. Features of the flora are determined with comparing to other regional floras.
Keywords: flora, ecobiologica, structure, Prisyvashya, the Crimea.